Digital Leadership in IT Organizations: A Narrative Review of Strategies and Challenges in the Era of Disruption - Prasetya, Yuli (Data : Journal of Information Systems and Management, 2025)
This narrative review investigates the evolving role of digital leadership in facilitating transformation within IT-driven organizations. The study aims to explore how digital leadership shapes strategic and operational changes amid accelerating technological advancements. A structured literature search was conducted across Scopus, Web of Science, and Google Scholar using key terms including "digital leadership," "organizational transformation," and "IT-driven management." The inclusion criteria emphasized peer-reviewed articles discussing leadership models in digital contexts across multiple sectors. The results reveal that transformational and collaborative leadership styles positively influence digital innovation, organizational agility, and employee engagement. Nonetheless, systemic barriers such as cultural resistance, bureaucratic inertia, and limited digital competencies impede successful implementation. International comparisons demonstrate that advanced economies benefit from robust digital infrastructure and policy frameworks, while developing countries face unique institutional and resource-related challenges. Case studies from education and healthcare sectors further underscore the critical role of leaders in aligning digital technologies with stakeholder needs. This review concludes that effective digital leadership is a cornerstone for driving sustainable change in modern organizations. Strategic policies focusing on cultural transformation, stakeholder communication, and capacity building are vital for overcoming institutional barriers. The findings contribute to the growing discourse on digital leadership by providing a foundation for further empirical and sector-specific research in this rapidly evolving domain